Diare Akut pada Balita di Puskesmas Tanah Kali Kedinding Surabaya - Yunita Ratri Adhiningsih; Alpha Fardah Athiyyah; Juniastuti Juniastuti (Sarana Ilmu Indonesia (salnesia), 2019)
Diarrhea is a disease that still be a health problem in the world, including Indonesia. The number of cases of diarrhea in children under five in East Java had increased in prevalence from 6.6% in 2013 to 10.7% in 2018. Deaths in diarrhea usually occurred as a result of severe dehydration which 70% -80% of them were children under-5 years. This study aimed to know the characteristics of children under-5 years who had acute diarrhea at Tanah Kali Kedinding Primary Health Care in September 2018 - January 2019. This type of research was a descriptive study, where the results was only a picture, using a cross-sectional approach. Statistical analysis was performed to describe the characteristics of each patient by using a frequency descriptive test. The results of this study found that in September 2018 - January 2019, of 116 children under-5 years suffering from acute diarrhea in the Tanah Kali Kedinding Health Care, Surabaya, most of them were females, within 1-2 years, had exclusive breastfeeding, had parents with the last education graduated from high school and family income under minimum of wage in Surabaya. It is hoped that this research will become a source of information for the Government and Primary Health Care to reduce the incidence of acute diarrhea.